In-depth analysis of OTC A208T case induced by OTC gene mutation and research on the prediction and simulation of the impact on protein function - Hu, Qingyang; Chen, Haiming; Liu, Tianyi; Dong, Xue; Hu, Xuejiao; Yan, Wenxin; Li, Zhong (Frontiers in Pediatrics, 2024)
Ornithine transcarbamylase deficiency (OTCD), a rare hereditary disease caused by gene mutation of ornithine transcarbamylase (OTC), is the most prevalent type among urea cycle disorders. OTCD typically leads to mitochondrial enzyme dysfunction, preventing the synthesis of citrulline from carbamoyl phosphate and ornithine, and is characterized by a remarkable increase in blood ammonia. Specific symptoms may include neurological abnormalities, growth retardation, and other manifestations.We presented a case of a child diagnosed with OTCD (OMIM: 311250). By using whole-genome sequencing (WGS) for the pedigree and in-depth whole-exome sequencing (WES), we aimed to identify the disease-causing genes. Gene mutation prediction tools were employed to verify the pathogenicity, and the molecular dynamics simulation method was utilized to assess the impact of this mutation on the activity and structural stability of the OTC protein.Whole-exome sequencing detected an OTC variant (NM_000531: c.622(exon6) G > A, p.A208T). Through comprehensive analysis with various gene mutation prediction tools and in line with the ACMG guidelines, this mutation site was firmly established as a pathogenic site. Moreover, the molecular dynamics simulation results clearly demonstrated that this mutation would significantly compromise the stability of the OTC protein structure.This study deepens our understanding of the clinical manifestations and characteristics of OTCD, especially the OTC A208T gene mutation site. Given the lack of specific clinical manifestations in OTCD patients, early and accurate diagnosis is crucial for effective treatment and prognosis improvement. To our knowledge, this is the first case of this mutation site reported in China.